2019
DOI: 10.1002/aet2.10334
|View full text |Cite
|
Sign up to set email alerts
|

Resident Supervision and Patient Care: A Comparative Time Study in a Community‐Academic Versus a Community Emergency Department

Abstract: Objective: The objective was to compare attending emergency physician (EP) time spent on direct and indirect patient care activities in emergency departments (EDs) with and without emergency medicine (EM) residents. Methods:We performed an observational, time-motion study on 25 EPs who worked in a community-academic ED and a nonacademic community ED. Two observations of each EP were performed at each site. Average time spent per 240-minute observation on main-category activities are illustrated in percentages.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…A recent study found that introducing residents into a community ED setting did not slow attending productivity because increased time spent teaching and supervising was balanced by the completion of administrative tasks by residents; this suggested a trade-off between education time and administrative time (one assumes these community physicians spent only as much time teaching as the decrease in administrative tasks allowed, since productivity was unaffected). 8 Our results fit with this pattern; when attendings spent less time on documentation they spent more time teaching, and vice versa. As academic departments weigh documentation expectations for faculty, they may wish to consider potential educational effects.…”
Section: Discussionsupporting
confidence: 76%
“…A recent study found that introducing residents into a community ED setting did not slow attending productivity because increased time spent teaching and supervising was balanced by the completion of administrative tasks by residents; this suggested a trade-off between education time and administrative time (one assumes these community physicians spent only as much time teaching as the decrease in administrative tasks allowed, since productivity was unaffected). 8 Our results fit with this pattern; when attendings spent less time on documentation they spent more time teaching, and vice versa. As academic departments weigh documentation expectations for faculty, they may wish to consider potential educational effects.…”
Section: Discussionsupporting
confidence: 76%
“…Prior research suggests that attendings work just as quickly when paired with medical students and may actually see more patients per hour when working with residents. [1][2][3][4] As technology -particularly electronic health records -re-shapes how physicians practice, 5 it is important to understand how on-shift teaching fits into the other activities expected of today's academic EP.…”
Section: Methodsmentioning
confidence: 99%
“…Bedside observations are limited, with emergency medicine clinical faculty spending as little as 1% of their time on-shift supervising interactions with non-critical patients. 3…”
Section: Importancementioning
confidence: 99%
“…Although emergency medicine attendings are in‐house at all hours, they are limited by the sheer volume of patients requiring care, and direct observation can limit efficiency and throughput. Bedside observations are limited, with emergency medicine clinical faculty spending as little as 1% of their time on‐shift supervising interactions with non‐critical patients 3 …”
Section: Introductionmentioning
confidence: 99%